Remaining Life of Flexible Pavement at Pulang Pisau – Pangkoh Road, Central Kalimantan - Siswoyo Siswoyo; Soerjandani P. Machmoed; Akbar B. K. Suharso (Journal of Civil Engineering, 2023)
The condition of the road pavement is an important aspect in terms of determining road maintenance and repair activities. In order to evaluate the condition of the road pavement, it is first necessary to determine the type of damage, the cause, and the extent of the damage that has occurred. Construction of a road that is not accompanied by good maintenance will cause various kinds of problems. Many district/city road pavements in Central Kalimantan have suffered damage as a result of repeated traffic loads, in line with increasing economic growth in these areas, including one of them on the Pulang Pisau – Pangkoh Road Section as far as ± 57.5 Km which is located in Pulang Pisau Regency, Central Kalimantan Province. So that on this road research will be carried out on the remaining existing road services to be able to provide alternative solutions for handling existing road problems and also budget plans. The method used in this study is using a FWD (Falling Weight Deflextometer) to determine the condition of the road structure. In addition, to find out how to handle it, this study used the 2017 Pavement Design Manual. Comprehensive road survey vehicles typically consist of a FWD mounted on a heavy truck together with a ground-penetrating radar and impact attenuator. The results obtained from this study are the remaining life of the Pulang Pisau – Pangkoh road section of 17% x UR (about 3-4 years). For its handling, it uses a flexible pavement overlay which was previously covered with selected fill and requires a cost of Rp. 243.905.730.000,- or Rp. 6.097.643.250,- per Km.